Acutely elevated O-GlcNAcylation suppresses hippocampal activity by modulating both intrinsic and synaptic excitability factors - Hwang, Hongik; Rhim, Hyewhon (Nature Publishing Group, 2019)
Post-translational modification (PTM) plays a critical role in increasing proteome complexity and diversifying protein functions. O-GlcNAc modification is a reversible, dynamic and highly abundant PTM catalyzed by a single pair of enzymes, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), regardless of substrates. The two enzymes are particularly enriched in the brain, and recent proteomic studies identified that a large number of neuron-specific proteins undergo O-GlcNAc modification. In addition, pathological conditions with aberrant O-GlcNAcylation such as diabetes and obesity are associated with the higher risk of cognitive decline and memory impairment. However, despite its prevalence in the brain, functional significance of O-GlcNAcylation in regulating neuronal properties remains unclear at the molecular level. Here, we report that an acute increase in O-GlcNAcylation induced by pharmacological inhibition of OGA significantly reduces the intrinsic excitability of hippocampal CA1 neurons through the cooperative modulation of multiple voltage-gated ion channels. Moreover, elevated O-GlcNAcylation also suppresses excitatory synaptic transmission at Schaffer collateral-CA1 synapses through the removal of GluA2-containing AMPA receptors from postsynaptic densities. Collectively, our findings demonstrate that a change in O-GlcNAcylation levels dynamically regulates hippocampal activity at both intrinsic and synaptic levels, providing a mechanistic link between dysregulated O-GlcNAcylation and hippocampal dysfunction.